Magnetic resonance imaging and intractable epilepsy: A systematic review - Al Shehri, Fahad (International Journal of Health Sciences, 2022)
Objective: Epilepsy is a chronic neurological disorder that occurs due to irregular neuronal activity in the central nervous system. The main job of a radiologist is to investigate the structural etiology in epilepsy patients. This study was undertaken to find out the importance of magnetic resonance imaging (MRI) in the screening of intractable epilepsy through a systematic search of literature. Methods: A systematic review was performed using the PRISMA guidelines. Peer-reviewed studies on MRI and intractable epilepsy were retrieved from MEDLINE, ScienceDirect and Google Scholar. Moreover, studies cited in the key articles were also screened to increase the sensitivity and specificity of the systematic search. Results: The database search till March 2022 found a total of 112610 articles. Out of them, only 10 highly selected articles were included in the study. The pooled data point out that the rapid development in MRI techniques and the functional MRI (fMRI) has now become more and more critical in the diagnosis and management of patients with epilepsy. In addition, the data also pointed out that MRI-based approaches are also very useful for post-operative epilepsy patients as it gives information about the quality of the surgery. The data collected showed that the MRI is the choice technique for the evaluation of patients with epilepsy. Conclusions: The applicability of MRI in epilepsy diagnosis is highly accessible in all over the globe. The pooled data concluded that the MRI-based surgical approaches are extremely useful for the surgeons to provide three-dimensional imaging with superimposed real-time pointer details that have proved successful for epilepsy patients.